Dari Biji ke Cita Rasa: Pelatihan Brewing dan Cupping untuk Pemberdayaan Petani Kopi Desa Bayan Kabupaten Lombok Utara - Mimi Cahayani; Alvin Juniawan; Rosalina Edy Swandayani; Arista Suci Andini; Kiki Fibrianto; Widya Dwi Rukmi; Erdiana Pangestuti (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to enhance the capacity of coffee farmer groups in post-harvest processing and professional coffee quality assessment, as well as to improve farmers’ understanding of coffee flavor profiles in order to increase their competitiveness in the market. The program was implemented through training and mentoring activities involving 35 coffee farmers from the “Muda Maju Tanjung Biru” group. Program evaluation was conducted using questionnaires and analyzed with a non-parametric statistical test (McNemar’s test). The results indicate that the training was effective in improving the partners’ knowledge and skills, as evidenced by a 79% increase in participants’ average knowledge scores after the program. In the cupping score training, 40% of participants (14 farmers) successfully achieved basic scoring competency. Overall, this community service program has proven to enhance farmers’ professionalism in coffee post-harvest processing and quality evaluation.